Mixed active and passive, heart rate-controlled heat acclimation is effective for paralympic and able-bodied triathletes - Stephenson, B. T.; Tolfrey, K.; Goosey-Tolfrey, V. L. (Frontiers in Physiology, 2019)
Purpose: The aims of this study are to explore the effectiveness of mixed active and passive heat acclimation (HA), controlling the relative intensity of exercise by heart rate (HR) in paratriathletes (PARA), and to determine the adaptation differences to able-bodied (AB) triathletes.